Progressive Triangles

Geometry Level 4

Find the number of different triangles that exist which have its angles in an arithmetic progression, have its sides in a geometric progression, and has at least one unit side.

None Two One Three Infinitely Many

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chris Lewis
Dec 25, 2019

The sides are in geometric progression; say they're a r , a , a r \frac{a}{r} ,a, ar .

The angles are in arithmetic progression, and sum to 180 ° 180° . Note this means the angle opposite the side of length a a must be 60 ° 60° .

By the cosine rule, a 2 = a 2 r 2 + a 2 r 2 2 a 2 cos 60 a^2=\frac{a^2}{r^2}+a^2 r^2 - 2a^2 \cos{60} .

Dividing by a 2 a^2 and substituting cos 60 = 1 2 \cos 60=\frac12 , we get 1 = 1 r 2 + r 2 1 1=\frac{1}{r^2}+r^2-1 , or ( r 1 r ) 2 = 0 \left(r-\frac{1}{r} \right)^2=0 . Hence r = 1 r=1 is the only solution, that is the only such triangle is the unit equilateral triangle.

Alternative (longer) solution below:

Let the sides of the triangle be a b c a \le b \le c and the angles opposite these sides be A B C A\le B\le C .

Since the angles are in arithmetic progression, and they sum to 180 ° 180° , they must be 60 θ , 60 , 60 + θ 60-\theta,60,60+\theta for some non-negative θ < 60 \theta<60 .

Since the sides are in geometric progression, they satisfy a b = b c \frac{a}{b}=\frac{b}{c} .

By the sine rule, sin A a = sin B b = sin C c \frac{\sin A}{a}=\frac{\sin B}{b}=\frac{\sin C}{c} . With a little rearrangement and cancellation, this becomes sin ( 60 θ ) sin ( 60 + θ ) = sin 2 60 = 3 4 \sin{(60-\theta)} \sin{(60+\theta)}=\sin^2 60=\frac34 .

Expanding, sin ( 60 θ ) sin ( 60 + θ ) = ( sin 60 cos θ sin θ cos 60 ) ( sin 60 cos θ + sin θ cos 60 ) = sin 2 60 cos 2 θ sin 2 θ cos 2 60 = 1 4 ( 3 cos 2 θ sin 2 θ ) = 1 4 ( 1 + 2 cos 2 θ ) = 3 4 \begin{aligned} \sin{(60-\theta)} \sin{(60+\theta)} &=(\sin{60} \cos{\theta}-\sin{\theta} \cos{60})(\sin{60} \cos{\theta}+\sin{\theta} \cos{60}) \\ &=\sin^2 {60} \cos^2 {\theta}-\sin^2 {\theta} \cos^2 {60} \\ &=\frac14 \left( 3\cos^2 {\theta}- \sin^2 {\theta} \right) \\ &=\frac14 (1+2\cos {2\theta})\\ &=\frac34 \end{aligned}

so that finally cos 2 θ = 1 \cos{2\theta}=1 and the unique solution is θ = 0 \theta=0 corresponding to an equilateral triangle; from the remaining given condition, the only such triangle is the unit equilateral triangle.

Nice solution!

David Vreken - 1 year, 5 months ago

Log in to reply

Haaaang on - just realised there's a much easier way (major edit coming up...)

Chris Lewis - 1 year, 5 months ago

Log in to reply

I used the law of cosines instead.

David Vreken - 1 year, 5 months ago

Let A B C ABC be the triangle with a = B C a=BC , b = C A b=CA and c = A B c=AB and A B C \angle A \le \angle B \le \angle C . Since the angles are in arithmetic progression, we have

B = A + C 2 = 18 0 B 2 B = 6 0 \angle B = \frac{{\angle A + \angle C}}{2} = \frac{{180^\circ - \angle B}}{2} \Rightarrow \angle B = 60^\circ .

Now, the relation A B C \angle A \le \angle B \le \angle C yields a b c a \le b \le c and since the sides are in geometric progression, we get

b 2 = a c sin 2 B = sin A sin C (by sine rule) sin 2 6 0 = sin A sin C sin A sin C = 3 4 cos ( A C ) cos ( A + C ) = 3 2 cos ( A C ) + cos B = 3 2 cos ( A C ) = 3 2 cos 6 0 cos ( A C ) = 1 ( A C ) = 0 (since 18 0 < ( A C ) < 18 0 ) A = C \begin{array}{l} {b^2} = a \cdot c \Rightarrow {\sin ^2}B = \sin A \cdot \sin C & {\color{#20A900}{\text{(by sine rule)}}}\\ \Rightarrow {\sin ^2}60^\circ = \sin A \cdot \sin C\\ \Rightarrow \sin A \cdot \sin C = \frac{3}{4}\\ \Rightarrow \cos \left( {A - C} \right) - \cos \left( {A + C} \right) = \frac{3}{2}\\ \Rightarrow \cos \left( {A - C} \right) + \cos B = \frac{3}{2}\\ \Rightarrow \cos \left( {A - C} \right) = \frac{3}{2} - \cos 60^\circ \\ \Rightarrow \cos \left( {A - C} \right) = 1\\ \Rightarrow \angle \left( {A - C} \right) = 0 & {\color{#20A900}{\text{(since }} - 180^\circ < \angle \left( {A - C} \right) < 180^\circ )}\\ \Rightarrow \angle A = \angle C \end{array}

This result leads to a unique solution, namely the (unit side) equilateral triangle.

The correct answer is one {\color{#D61F06}{\text{one}}} .

Nice solution!

David Vreken - 1 year, 5 months ago
David Vreken
Dec 27, 2019

Since the angles are in an arithmetic progression, we can label them a d a - d , a a , and a + d a + d . The angle sum of a triangle is 180 ° 180° , so ( a d ) + a + ( a + d ) = 180 ° (a - d) + a + (a + d) = 180° , which solves to a = 60 ° a = 60° , its medium angle.

Since the sides are in a geometric progression, we can label them x r \frac{x}{r} , x x , and r x rx .

The medium side x x must be across its medium angle a = 60 ° a = 60° , so by the law of cosines, x 2 = ( x r ) 2 + ( r x ) 2 1 2 x r r x cos 60 ° x^2 = (\frac{x}{r})^2 + (rx)^2 - \frac{1}{2} \cdot \frac{x}{r} \cdot rx \cdot \cos 60° , which rearranges to 0 = ( r 2 1 ) 2 0 = (r^2 - 1)^2 and has one real solution r = 1 r = 1 .

Since r = 1 r = 1 , the three sides must all be the same, so it must be an equilateral triangle (and therefore d = 0 d = 0 ), and there is only one possible equilateral triangle with at least one unit side.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...